GILBERT SYNDROME: GENETIC FACTORS AND DIAGNOSTIC APPROACHES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Gilbert syndrome (GS) is an inherited disorder of bilirubin metabolism characterized by unconjugated hyperbilirubinemia. The condition is associated with a mutation in the promoter region of the UGT1A1 gene, which encodes the enzyme uridine diphosphate-glucuronosyltransferase 1A1. Although often asymptomatic, accurate diagnosis of GS is important to prevent misdiagnosis, unnecessary investigations, and overtreatment.